Assessing and mitigating wastewater-related health risks in low-income countries: an introduction - Bos, R.; Carr, R.; Keraita, Bernard N. (2010)
In and around urban areas pollution of natural water bodies is on the rise. As a result, wastewater irrigation is an increasingly common reality around most cities in the developing world. For reasons of technical capacity or economics, effective treatment may not be available for years to come; therefore, international guidelines to safeguard farmers and consumers must be practical and offer feasible riskmanagement options. This chapter provides an introduction to microbiological hazards. These can be addressed best in a step-wise risk assessment and management approach starting with wastewater treatment where possible, and supported by different pathogen barriers from farm to fork. A major change in the most recent WHO Guidelines for the safe use of wastewater, excreta and greywater in agriculture and aquaculture (WHO, 2006) agriculture is the focus on a holistic approach to achieving health-based targets, instead of prescribing irrigation waterquality threshold levels that are often unattainable. The health-based targets should not be read as absolute values but as goals to be attained in the short, medium or long term depending on the country?s technical capacity and institutional or economic conditions. Local standards and actual implementation should progressively develop as the country moves up the sanitation ladder. While healthrisk assessments are recommended to identify entry points for risk reduction and health-based targets, the Guidelines also offer shortcuts in situations where research capacities and data are constrained.